The KKN-T Program as a Form of Community Service: Optimizing Vacant Land through the Planting of Medicinal Plants in the Pematang Gubernur Subdistrict - Muhammad Hariqbal Dewantara; Aditya Muhammad Soleh; Aziz Jafar Shidiq; Yola Khairunisa; Syisva Nurwita; Merry Rullyanti; Tita Septi Handayani (Universitas Dehasen Bengkulu, 2026)
Unused land in RT 25 RW 05, Pematang Gubernur Village, has the potential to be developed into a green space that benefits family health and improves the quality of the residential environment, but until now it has not been utilized optimally. This community service program aims to maximize the use of vacant land by planting medicinal plants that are easy to grow and useful for daily needs. The implementation of activities consisted of an initial survey in collaboration with local administrators, mapping the planting area, providing counseling on the benefits of medicinal plants and simple cultivation methods, land preparation and planting media practices, planting seedlings together, and periodic maintenance assistance according to the residents' picket schedule. Evaluation was carried out by comparing the level of knowledge before and after the counseling, observing plant growth, and assessing residents' active participation in the activity. The results of this activity showed an increase in residents' understanding of how to select medicinal plants, planting methods, and care; the establishment of a medicinal plant garden area on the vacant land in RT 25 RW 05; and increased community participation in maintaining cleanliness and garden maintenance. The approach of optimizing vacant land through planting medicinal plants has been proven to provide an effective participatory way to increase family health independence and create a greener and more productive residential environment.